Conoscenza e etica in Richard Rorty - Romano, Emilia (Studi sulla Formazione/Open Journal of Education, 2011)
The era in which we live, characterized by multiculturalism and complexity, it is a time when it is clear the difficulty of man to orient and to choose their own way. It’s the time of the fall of every certainty, is the era of “post”, after the tradition, after metaphysics, after the truth, and that requires more effort than any other constant reflection. The neopragmatismo seems to be an effective investigative tool for conducting this reflection and a vantage point to carry on a conversation around the issues of education. In particular, the author intended to refer to the work of Richard Rorty, the author who more than others reflected on the encounter between two important pragmatist tradition: that of classical pragmatism and the “continental” or responsible for the development of a new European concept of truth, understood as a critical and interpretative.